NEUROPSYCHIATRIC ADVERSE EFFECTS OF HVC TREATMENT AND THEIR IMPACT ON THE TREATMENT RESPONSE - Sadia Qureshi; MH Qazi; Muhammad Tahir Aziz (Journal of University Medical & Dental College, 2017)
Objective: Hepatitis C (HC) is an infectious disease of the liver and is associated with multiple complications. It has been reported that the medicines, which are being used to treat HC, cause neuropsychiatric adverse effects like depression, sleep disturbances, insomnia and irritability. Moreover, hepatitis C virus (HCV) infection itself is also strongly associated to psychiatric disorders. This study was conducted to check the impact of these neuropsychiatric adverse effects on treatment outcome. Method: A prospective study was designed to look for the neuropsychiatric adverse effects in HCV genotype 3a infected patients, as HCV 3a is on the top to causeHCV infection in South East Asian population, when treated with Interferon alpha and ribavirin (INF + RV) or pegylated interferon alpha and ribavirin (Peg INF + RV) and their effects on treatment outcome. Results: This study was conducted in two different public hospitals of Lahore. It was found that these patients had depression, anxiety, emotional lability, irritability and insomnia. It was also observed that the patients who were treated with INF + RV had higher frequency of neuropsychiatric adverse effects. Moreover, when we compared the occurrence of these adverse effects with other populations our study group had much lower frequency. Conclusion: It was concluded that a multidisciplinary tam approach with timely strategies could improve the treatment outcome of HC patients.